The Application of the Technology Readiness Acceptance Model on Education - Nafia, Zidnii Ilma; Hidayati, Dian; Sulisworo, Dwi (Journal of Novel Engineering Science and Technology, 2023)
The development of science and technology has changed the work system, including in educational institutions. Rapid information and communication technology changes are now essential factors in changing education management. Improving the quality of education can leverage the quality of a nation. Technology in the teaching field provides many opportunities in various aspects of education and learning, such as academic services, access to learning materials, educational evaluation, management of lesson content, reports on student learning outcomes and the use of digital-based learning media by teachers. The use of technology in learning can create a competitive environment for students and teachers to be more creative and innovative. Education in Technology Study (Edtech) has become a global concern, especially during a pandemic. The revitalization and development of teacher and student synergy in implementing digital technology-based education will accelerate the education revolution 4.0.